2017
DOI: 10.1182/bloodadvances.2016003632
|View full text |Cite
|
Sign up to set email alerts
|

Clonal evolution underlying leukemia progression and Richter transformation in patients with ibrutinib-relapsed CLL

Abstract: Key Points• Del(18p), together with del(17p)/TP53 mutations, is present at a high frequency before ibrutinib treatment.• BTK mutations drive ibrutinib relapse, but del(17p)/TP53 mutations may be dispensable.Ibrutinib has generated remarkable responses in patients with chronic lymphocytic leukemia (CLL), including those with an unfavorable cytogenetic profile. However, patients develop resistance, with poor outcomes and no established treatment options. Mutations in BTK and PLCG2 have emerged as main mechanisms… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
141
0
4

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 111 publications
(150 citation statements)
references
References 44 publications
5
141
0
4
Order By: Relevance
“…The frequency of BTK and PLCG2 mutations in RT is different than the frequency of such mutations in patients who have progressive CLL on ibrutinib without transformation. In the peripheral blood, BTK and PLCG2 mutations are found in about 80% of patients with progressive CLL (Table 1) but only about 40% of patients with RT [5, 11]. Likely due to the greater difficulty in obtaining transformed tissue, the molecular details of the Richter’s tissue remain largely unexplored to date.…”
Section: Reasons For Discontinuation Of Ibrutinib Therapymentioning
confidence: 99%
See 4 more Smart Citations
“…The frequency of BTK and PLCG2 mutations in RT is different than the frequency of such mutations in patients who have progressive CLL on ibrutinib without transformation. In the peripheral blood, BTK and PLCG2 mutations are found in about 80% of patients with progressive CLL (Table 1) but only about 40% of patients with RT [5, 11]. Likely due to the greater difficulty in obtaining transformed tissue, the molecular details of the Richter’s tissue remain largely unexplored to date.…”
Section: Reasons For Discontinuation Of Ibrutinib Therapymentioning
confidence: 99%
“…Likely due to the greater difficulty in obtaining transformed tissue, the molecular details of the Richter’s tissue remain largely unexplored to date. However, one study has reported that three out of six cases of RT displayed BTK mutations in the nodal tissue [11]. The different BTK/PLCG2 mutational frequency in RT suggests an underlying biology that is distinct from simple progression of CLL without transformation (discussed below).…”
Section: Reasons For Discontinuation Of Ibrutinib Therapymentioning
confidence: 99%
See 3 more Smart Citations